A rectifying diode with hysteresis effect from an electroactive hybrid of carbazole-functionalized polystyrene with CdTe nanocrystals via electrostatic interaction - Liu, Juqing (2013)
One of the strategies to tune current-voltage behaviors in organic diodes is to combine field-induced charge transfer processes with schottky barrier. According to this principle, a rectifying diode with hysteresis effect was fabricated utilizing a hybrid of electroactive polystyrene derivative covalently tethered with electron-donor carbazole moieties and electrostatic linked with electron-acceptor CdTe nanocrystals. Current-voltage characteristics show an electrical switching behavior with some hysteresis is only observed under a negative bias, with three orders of On/Off current ratio. The hybrid material based rectifier exhibits a rectification ratio of six and its maximum rectified output current is about 5 × 10−5 A. The asymmetric switching is interpreted as the result of both field induced charge transfer and schottky barrier, capable of reducing the misreading of cross-bar memory. Meanwhile, chemical doping of CdTe nanocrystals instead of physical blend favor their uniform dispersion in matrix and stable operation of device.